Regulation of banks under Basel frameworks - Miškovič, Branislav (2011)
This diploma thesis provides a high-level overview of banking regulation under the general rules of the Basel agreements that are followed in almost every international bank globally. The introductory part of this paper is devoted to the fundamental purpose of regulation and explains the risks banks are exposed to. The following chapters outline the evolution of banking regulation as agreed by the Basel committee, explain the various capital adequacy frameworks, risk measurement methodologies and look into the proposed future developments in the regulatory area, including ex-post (Basel I, II) and ex-ante analysis of the practical impacts on banks. The final part of this diploma work is focused on actual real world application of the Basel II rules in a banking organization, precisely Barclays Capital, the investment banking arm of Barclays Plc. headquartered in London, UK and regulated by the Financial Services Authority (FSA).